Teratologische Untersuchungen an Ameisen (Hymenoptera: Formicidae). - Buschinger, Alfred; Stoewesand, Heide (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Material containing 97 ants with deformities, chiefly of the subfamily Myrmicinae, is described. Besides eleven gynandromorphs there are two atavistic specimens. The other deformities were probably caused by injuries at an early stage of development. Faulty segmentation of the antennae was observed in 15 males. Fusion of body segments and cleavage of the sclerites occurred chiefly in the region of the stalks; its centre is mostly dorsal. The possibilities of the origin and the preservation of such deformed individuals in the social insect state are discussed.